Manhaj Tahlili dan Muqaran - Jumaedi Nagga; Muhammad Idris (AL-AQWAM: Jurnal Studi Al-Quran dan Tafsir, 2022)
The purpose of this study is to develop tahlili and muqaran methods using four existing research methods.The data collection technique used in this study as a whole is literature research, or book survey. Data is processed using qualitative methods, namely processing data based on the values contained in each data set. The findings revealed that there is a distinguishing feature that other interpretations lack, namely the tendency of interpretation to follow the pattern of language (lughawi). This is demonstrated by (1) Writing down points that did not exist in the previous interpretation, (2) Explaining each I’jaz al-Qur’an in detail and containing it in a separate book, (3) Revealing arabic linguistic values (balaghah, nahwu, saraf, and mantiq), and (4) Clearly revealing the language style (badi’) contained in a Qur’an sentence by explaining how to use it. (4) Explaining the harmony of one verse with another.